2006
DOI: 10.1002/qua.21132
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of cooperative effects in the homo‐ and heteromeric hydrogen bond chains (HCN)nHF withn= 1, 2, and 3

Abstract: Theoretical investigations concerning the formation of hydrogen bonds in both homomeric, (HCN) n , and heteromeric clusters of the type (HCN) n OHF (n ϭ 1, 2, and 3) have been performed through ab initio molecular orbital calculations at the second-order Møller-Plesset (MP2) and density functional theory (DFT)/B3LYP levels, with the 6-311ϩϩG(d,p) basis set. The formation of hydrogen bonds is investigated in terms of changes in structural, electronic, and vibrational parameters of the free species. Important pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It is especially important to point out that these ΔE C values are not the essence of the hydrogen bond strengths because the energies of the IV and V complexes are uncooperative. In other words, the total energy values of −247.14216984 H and −247.14384609 H cannot be divided equally among the unsymmetrical hydrogen bonds-N···H d and N···H c of IV, as well as N···H d , N···H g , and N···H a' of V-as already reported in several studies on the formation of cluster systems [86][87][88]. The ternary complexes, IV and V, are formed by two and three hydrogen bonds, respectively, where, in addition to the predominance of the electrostatic potential [89] already quoted here, it is well-known that charge transfer is one of the most important effects in intermolecular interactions [90].…”
Section: Structurementioning
confidence: 55%
“…It is especially important to point out that these ΔE C values are not the essence of the hydrogen bond strengths because the energies of the IV and V complexes are uncooperative. In other words, the total energy values of −247.14216984 H and −247.14384609 H cannot be divided equally among the unsymmetrical hydrogen bonds-N···H d and N···H c of IV, as well as N···H d , N···H g , and N···H a' of V-as already reported in several studies on the formation of cluster systems [86][87][88]. The ternary complexes, IV and V, are formed by two and three hydrogen bonds, respectively, where, in addition to the predominance of the electrostatic potential [89] already quoted here, it is well-known that charge transfer is one of the most important effects in intermolecular interactions [90].…”
Section: Structurementioning
confidence: 55%
“…Arauju et al showed that the cooperative effect in hetero hydrogen-bonded chains was greater than that for homo chains for a series of (HCN) n -HF and (HCN) n (n = 1, 2, 3) clusters [71]. Additionally, as the chains become longer there was a corresponding increase in the cooperative effects observed [71].…”
Section: Interplay Between Non-covalent Interactionsmentioning
confidence: 86%
“…Interestingly, the hydrogen bond strength in the decamer was about 160 % higher than in the dimer, despite the hydrogen bonds being 3-center hydrogen bonds as opposed to being typical 2-center hydrogen bonds [70]. Arauju et al showed that the cooperative effect in hetero hydrogen-bonded chains was greater than that for homo chains for a series of (HCN) n -HF and (HCN) n (n = 1, 2, 3) clusters [71]. Additionally, as the chains become longer there was a corresponding increase in the cooperative effects observed [71].…”
Section: Interplay Between Non-covalent Interactionsmentioning
confidence: 94%
“…in (a) indicates a loss of charge in the C-C bond. Although is not cooperative 67 , the value of -0.016 e.u. shows a receiving of charge in H. For (b) and (c) complexes, the diminutions of charge of +0.052 e.u.…”
Section: Intermolecular Energiesmentioning
confidence: 93%